Physico-chemical changes in pechay (Brassica chenensis Linn) stored at room and refrigerator temperatures - Garde, Ma. Lourdes O. (1978)
Pechay, of the Native Green Leaf Variety, was stored at room temperature (89.6 to 92.0°F) and refrigerator temperature (60.8° to 64.4°F). Daily examinations were made on the respiration rate, weight, chlorophyll content, reducing sugars, and vitamin C content for 7 days to determine the effect of storage temperature on the physical and chemical properties of pechay. The weight, chlorophyll and vitamin C contents were found to decrease during storage at both temperatures. These changes, however, proceeded at a faster rate at room temperature than at refrigerator temperature. The reducing sugars tended to increase at refrigerator temperature while the reverse took place at the higher temperature. The respiration rate was observed to increase at room temperature and decrease at refrigerator temperature.